Performance Analysis of MANET Routing Protocols using different Mobility Models and Varying Speed - Prof. Ashwini S. Hanwate, (International Journal of Scientific Research in Science and Technology, 2024)
A mobile ad-hoc network is a continuously self-configuring, infrastructure less, network of mobile devices. It is the network of mobile nodes without any fixed topology. In this network, each node acts as both hosts and router simultaneously. Each device in a MANET is free to move independently in any direction, and will therefore change its link to other devices frequently. In such a network there are lots of possibilities of mobility of nodes. Therefore mobility of nodes is challenging issue for designer. We have surveyed comparative performance analysis of different routing protocols. Under the different mobility models in term of Packet Delivery Ratio, Average End to End Delay. We have carefully studied the behavior of these routing protocols and compared their performance in different scenarios based. This paper defines which protocol to use in different cases such as if time is important or if data is important in various mobility modes such as all node mobility, destination node mobility and source node mobility and proposed the new algorithm on the basis of protocols evaluation in different situation.
Keywords: Ad-hoc Network; MANET; Mobility